LINGUISTIC AND PRAGMATIC APPROACHES TO ACHIEVING COMMUNICATIVE GOALS IN THE TRANSLATION OF ENGLISH AND UZBEK MEDICAL TEXTS - Ra’no Movlanova (Scholar Express Journals, 2025)
This article examines the linguistic and pragmatic strategies used to achieve communicative effectiveness in the translation of oncology-related medical texts between English and Uzbek. The translation of specialized medical texts, particularly in oncology, presents unique challenges due to the complexity of terminology, cultural differences, and varying levels of medical knowledge among audiences. The study highlights key linguistic features such as terminology consistency, grammatical adaptations, and stylistic adjustments. Pragmatic considerations, including cultural sensitivity, audience awareness, and clarity, are also analyzed. Recommendations are provided to improve translation quality, ensuring accurate and culturally appropriate communication in medical contexts. This research emphasizes the critical role of tailored translation strategies in enhancing the comprehension and accessibility of medical information across languages
Keywords: medical translation; oncology texts; linguistic strategies